Labelisasi Portal Berita Kompas.com terhadap Jennifer Dunn - Dwi Ira Ningrum Ana Mardiana (Badan Pengembangan dan Pembinaan Bahasa, 2020)
This paper discusses Kompas.com news labelling toward Jennifer Dunn. The research questions that discussed in this paper are how does the form of lexical choices in labelling